Pretreated palm oil clinker as an attached growth media for organic matter removal from synthetic domestic wastewater in a sequencing batch reactor - Baker Nasser Saleh Al-dhawi; Shamsul Rahman Mohamed Kutty; Aiban Abdulhakim Saeed Ghaleb; Najib Mohammed Yahya Almahbashi; Anwar Ameen Hezam Saeed; Al-Baraa Abdulrahman Al-Mekhlafi; Yaser Abdulwahab Ali Alsaeedi; Ahmad Hussaini Jagaba (Case Studies in Chemical and Environmental Engineering, 2023)
Attached-growth systems are biological wastewater treatment processes with biomass attached to a media for organic matter and nutrient removal from wastewater. In this regard, bioreactors containing biocarriers have been successful by far with few limitations. The impact of bio-carrier materials type and properties on wastewater treatment is one important aspect that needs attention. Different synthetic materials have been utilized. However, this study utilized waste palm oil clinker (POC) as a biocarrier in a sequencing batch reactor (SBR) for syntheticdomestic wastewater treatment. This is to work in line with the attainment of sustainable development goals (SDGs). In this study, the POC was used as a biocarrier submerged in the aeration tank of bioreactor A of an attached growth system. Whereas the bioreactor B acts as a control. The overall working volume of the bioreactor systems was 10 L each. The treatment efficiency was measured by differing the hydraulic retention time (HRT) while organic contaminants were monitored. The HRT was varied at 6, 12, 24, 48, and 72 hours with the organic loading rate (OLR) kept constant at 550 mg/L.d. At all conditions of HRT (6–72 hours), minimum and maximum COD removals were up to 80% and 95.4% respectively. The influence of HRT was found to be more affected. Several biokinetic models, that includes the First order and Stover-Kincannon, were fitted to the steady-state data collected at different HRTs. The COD R2 values of 0.9096 and 0.9269 were obtained for reactors A and B, respectively. The maximum removal rate constant (μmax) and the saturation value constant (KB) for the Stover-Kincannon, were observed as 0.0005 g/L.d and 1 g/L.d, respectively for the bioreactor A. Throughout the study, POC incorporated SBR system demonstrated higher treatment efficiency compared to the control reactor in terms of COD removal. Thus, findings from this study have the potential to answer SDGs 6, 9, and 14.